Hydroponics gel as a new electrolyte gelling agent for alkaline zinc-air cells - Yahaya, A.H.; Arof, Abdul Kariem; Othman, R.Y.; Basirun, Wan Jefrey (Elsevier, 2001)
The viability of hydroponics gel as an alkaline electrolyte gelling agent was analyzed. Zinc-air primary cells with a low concentration of aqueous potassium hydroxide (KOH) electrolyte and a hydroponics gel as an electrolyte gelling agent were prepared for this purpose. The oxygen reduction process involved a rate-limiting stage which affected the reaction kinetics and the cell performance. X-ray diffraction (XRD) measurements were undertaken on both the zinc anode and the air cathode before assembly in the cell. It was found that the inclusion of hydroponics gel into the aqueous KOH electrolyte didn't affect the electrochemistry of the zinc-air cell.